2008
DOI: 10.1021/mp800093f
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Gene Silencing for Inhibiting Apoptosis in Insulinoma Cells and Human Islets

Abstract: Abstract:Although islet transplantation has great potential to treat type I diabetes, most islet grafts do not function due to the host immune rejection, nonspecific inflammatory response and poor revascularization. Since caspase-3 plays a crucial role in apoptosis of transplanted islet cells, we used chemically synthesized small interfering RNAs (siRNAs) to silence caspase-3 in insulinoma (INS-1E) cells and human islets, and then determined whether caspase-3 gene silencing can prevent these cells from cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 28 publications
(55 reference statements)
4
54
0
Order By: Relevance
“…Two of the most important limitations to the widespread of human islet transplantation are the limited supply of islets for transplantation and the inadequate means for preventing islet loss after transplantation [2]. Moreover, because of the extensive posttransplantation challenges, a patient needs at least 10,000 islet equivalents (IEs) per kilogram of body weight (extracted from two or more donor pancreases) for an optimal transplantation outcome, making the current shortage in islet supply even worse [3,6]. The major reasons for islet graft failure and useful interventions are listed in Table 1-1.…”
Section: Challenges Of Human Islet Transplantationmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the most important limitations to the widespread of human islet transplantation are the limited supply of islets for transplantation and the inadequate means for preventing islet loss after transplantation [2]. Moreover, because of the extensive posttransplantation challenges, a patient needs at least 10,000 islet equivalents (IEs) per kilogram of body weight (extracted from two or more donor pancreases) for an optimal transplantation outcome, making the current shortage in islet supply even worse [3,6]. The major reasons for islet graft failure and useful interventions are listed in Table 1-1.…”
Section: Challenges Of Human Islet Transplantationmentioning
confidence: 99%
“…For example, Giannoukakis et al first reported that adenoviral gene transfer of interleukin 1 receptor antagonist (IL-1Ra) prevented IL-1β-mediated nitric oxide production from human islets in vitro as well as the suppression of insulinproducing β cell function as determined by glucose-stimulated insulin production [3]. In our lab, Narang et al and Panakanti et al combined the gene expression of vascular endothelia growth factor (VEGF) and IL-1Ra to improve the therapeutic effects of single gene therapy while Li et al and Cheng et al targeted downstream pro-apoptotic factors of IL-1β pathway and used small heparin RNA to inhibit the expression of iNOS and caspase 3, respectively [4][5][6][7]. During the time we worked on the apoptosis of human islets, we identified a potent anti-apoptotic factor X-linked inhibitor of apoptosis (XIAP), which binds to and inhibits caspase 3, 7 and 9 at the same time.…”
Section: Progress In Gene Therapymentioning
confidence: 99%
See 3 more Smart Citations